The Acute Temporary Peritoneal Dialysis in Neonates: A Five-Year Experience - Seyedeh Fatemeh Khatami; Hasan Boskabadi; Pouya Parvaresh (Mashhad University of Medical Sciences, 2015)
Background: The aim of this prospective study was to evaluate the characteristics of patients, treated by acute peritoneal dialysis (PD). We also assessed the indications for PD, PD-associated complications and neonatal outcomes in our patients. Methods: During five years, 30 term newborns underwent temporary cycling PD. The procedure was performed by applying the manual technique. A straight and relatively rigid peritocat catheter (Germany) was percutaneously inserted in neonates. Statistical analysis was performed, using Chi-square and student's t-test. Results: All subjects were term newborns, including 16 females (52%) and 14 males (48%). In total, 16 cases (52%) were born via cesarean section. The average age and weight of neonates at catheter insertion were 15 days (range of 5-26 days) and 2800 g (range of 2300-4060 g), respectively. The mean PD duration was two days. There was no significant difference between gender, weight, mode of delivery and associated complications. In total, 74% of patients needed assisted ventilation. No case of death was reported due to catheter insertion; however, 12 patients (40%) died during PD. PD-related complications were reported in 70% of patients, and the most common complication was catheter outflow failure (14 cases, 46%). The underlying causes included inborn errors of metabolism (16 cases, 52%) and acute renal failure (14 cases, 48%). Urea cycle enzyme defect, along with hyperammonemia, was the most common etiologic disease (9 cases). Conclusion: PD is an effective treatment for seriously ill newborns with life-threatening conditions such as acute renal failure or certain inborn errors of metabolism. However, mortality rate remains high due to the severity of underlying diseases and comorbidities.